Mouse Thalamic Differentiation: Gli-Dependent Pattern and Gli-Independent Prepattern - Haddad-Tóvolli, Roberta; Heide, Michael; Zhou, Xunlei; Blaess, Sandra; Alvarez-Bolado, Gonzalo (Frontiers in Neuroscience, 2012)
Sonic hedgehog (Shh) is essential for ventral neural tube development. The Gli transcription factors act downstream Shh—while Gli2 is the major activator (GliA), Gli3 acts primarily as a repressor (GliR). Remarkably, the thalamus, a dorsal region, develops close to the mid-diencephalic organizer, a unique dorsal Shh source. This lends complexity to the Shh-Gli interactions, suggesting the presence of a dorsal Gli activator elsewhere found only ventrally, and making the dissection of thalamic Gli functions particularly interesting. A current model postulates reciprocal antagonism of Shh and Gli3 in dorsal brain regions. To approach the thalamic role of Gli factors we first analyzed Gli2 and Gli3 mutants. In Gli2 mutants, the thalamus is small and poorly differentiated with the exception of the medial and intralaminar nuclei which, in contrast, are specifically and severely affected by Gli3 inactivation. Gbx2 expression is very reduced in the Gli3 mutant. Most thalamic nuclei are present in both mutants, although incompletely differentiated. The ventral posterior group, revealed by marker Hes1, is present in both mutants and extends axons to the telencephalon. To test the Gli3/Shh interaction we used a novel mutant lacking Gli3 and neuroepithelial Shh. The n-Shh/Gli3 thalamus is very large and very poorly differentiated except for a broad domain of Gbx2-Lhx2-Calb2 expression. In utero electroporation experiments on wildtype embryos suggest that a stage-specific factor acting early is responsible for this prepattern. We show that, in the thalamus, GliA acts downstream Shh to specify thalamic nuclei except the medial and intralaminar. Gli3A can partially substitute for Gli2A in the Gli2 mutant. GliR is essential for specification and growth of the medial and intralaminar nuclei, contributes to the specification of other thalamic nuclei and reduces thalamic size. Finally, GliA (from neuroepithelial Shh signaling) and GliR are not reciprocally antagonic in the thalamu